Pengembangan Model Semantik Ontologi Pada Domain Kendang Bali - Yasa, I Ketut Gede Udha Krisna; Dwidasmara, Ida Bagus Gede; Arya Kadyanan, I Gusti Agung Gede (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2022)
Traditional musical instruments are a form of representation of the cultural identity of each region. Traditional musical instruments are created in different forms and functions in each use. The activity of playing traditional musical instruments for the community is one form of art that is born from within. Art itself is one of the cultural heritages, which is better known as regional arts which are passed down from generation to generation. Traditional musical instruments have their own characteristics, such as the example of the Balinese Kendang musical instrument. Balinese kendang is one of the musical instruments that is closely related to the art of karawitan. Kawawitan art in short is the art of sound by processing the sounds of objects or musical instruments (instruments) in a traditional gamelan way. Kendang is played by slap with the palm of the hand. The drum instrument belongs to the middle class, which functions as the leader of a gamelan barungan. In Bali drum instruments are usually played in pairs and individually. If played in pairs, the drums are called drums lanang and wadon. In this digital era, many people, especially Balinese people, are only limited to knowing the term Balinese drums without knowing the types or other meanings contained in them. Along with the times, many people are more interested in modern musical instruments so that traditional musical instruments are slowly being forgotten. The use of ontology as a documentation or representation technique is a solution to this problem. Ontology in the semantic web is a catalog where schemas are created using ontologies. Ontology is needed because it is useful for improving the development of semantic web applications. The ontology for Balinese cultural heritage, Balinese instruments or gamelan especially Balinese Kendang, can be used to document and represent knowledge surrounding the Balinese Kendang domain and also make knowledge about Balinese Kendang not only tacit but explicit.